Epidemiological profiles and causes of sudden deaths of various ages in Ethiopia: an autopsy-based study [version 2; peer review: 1 approved, 2 approved with reservations] - Sesen Tsegaye Tekle; Alemayehu Shiferaw Lema (F1000Research, 2025)
Background Sudden death is an important global public health issue. An autopsy is an important source of epidemiological data, as the considerable causes of sudden death remain hermetic until postmortem examination. This study is devoted to evaluating the sociodemographic, behavioral, clinical and pathological characteristics of sudden deaths of various ages in Ethiopia. Methods This is an observational, prospective, descriptive study that included all sudden deaths observed over 1 year at St. Paul’s Hospital and Millennium Medical College, Addis Ababa, Ethiopia. Results Sudden death (n = 568) accounted for 11.5% (95% CI: 10.6-12.4) of all autopsied cases. There were 482 males and 86 females (M:F ratio of 5.6:1) and a mean age of 44.8±17.349. The peak age group was the fourth and fifth decades, accounting for 43.9% of the cases. Chronic substance abuse and a history of prior illness were declared in 40.1% and 38% of cases of sudden death, respectively. Cardiovascular (36.1%), respiratory (32.6%), and gastrointestinal system (19.5%) pathologies were the most common causes. The leading underlying causes of sudden death were ischemic heart disease and pneumonia. Most (86.6%) sudden deaths occurred outside of a hospital setting. Conclusions Most of the causes of sudden death in Ethiopia can be prevented and treated. The majority of sudden deaths are silent without preexisting symptoms. Therefore, it is vital to develop public health measures that will help educate the community about the importance of recognizing the manifestation of various clinical conditions and the need to seek immediate clinical help. Furthermore, efforts should be made to make healthcare facilities accessible and affordable with adequate diagnostic and management capacity. Documentation of autopsy-based data could provide important epidemiological information to guide medical services, prevention efforts, and control measures.